A cause for nervousness: The proposed Māori land reforms in New Zealand - Warbrick, Paerau (AlterNative: An International Journal of Indigenous Peoples, 2016)
This commentary reflects upon the major Māori land reforms in te Ture Whenua Māori Bill (2016). The reforms implement more bureaucracy and replace some mechanisms used by the Māori Land Court to protect against Māori land loss. The Waitangi Tribunal, which has dealt with Māori grievances over land loss for over 30 years, issued a critical report in March 2016 along with recommendations about the reforms. That report was largely ignored by the New Zealand Government. This commentary contains a review of the literature on Māori land to date, as it helps to understand the ideas behind the Tribunal's report as well as the reforms. There is also an examination of the main points made by the Waitangi Tribunal, as well as aspects of te Ture Whenua Māori Bill (2016). The overall conclusion is that the Māori people should be very nervous about the reforms for their lands.
Keywords: land; land loss; land reforms

Reflections: Land is Never Just Land - Bargh, Maria; Weavers, Lydia (Women Talking Politics 2019, 2019)
Keywords: land; resource management; te ao Māori